Computer processing of remotely-sensed images [electronic resource] : an introduction / Paul M. Mather and Magaly Koch. - Mather, Paul Michael (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2011., 2018)
1 online resource (xx, 434 p.) : ill. (some col.), maps (some col.)